Mudharabah Pada Baitul Mal Wat Tamwil Sidogiri Cabang Pembantu Waru Sidoarjo - Shania Putri Ayu; Via Ratnasari; Dewi Audrynita; Affrido Galuh Mulyono (Maliyah : Jurnal Hukum Bisnis Islam, 2019)
Abstract: The Sidogiri Integrated Joint Business BMT Cooperative, abbreviated as "Koperasi BMT UGT Sidogiri" began operating on 5 Rabiul Awal 1421 H or 6 June 2000 AD in Surabaya and then obtained a Cooperative Legal entity from the Regional Office of the PK and M Cooperative Office of East Java Province with a decree Number: 09 / BH / KWK.13 / VII / 2000 dated 22 July 2000. There are two products at BMT UGT Sidogiri Waru, namely: financing products and savings products. The mudharabah agreement at BMT Sidogiri is used for savings products consisting of general sharia savings, al-haromain savings, umrah al-hasanah savings, Eid al-Fitr savings, qurban savings, savings from student care institutions, term mudharabah savings, and term mudharabah savings. Based on the analysis of Islamic law, the practice of mudharabah at BMT Sidogiri has fulfilled the pillars and requirements of mudharabah. Customers as shahibul mal and BMT as mudharib, capital, and ratio are also explained in detail in each product, the consent of the qabul is contained in the contract and BMT Sidogiri has the authority to manage customer funds. Keywords: Mudharabah, BMT Sidogiri, Islamic Law Abstrak: Koperasi BMT Usaha Gabungan Terpadu Sidogiri disingkat “Koperasi BMT UGT Sidogiri” mulai beroperasi pada tanggal 5 Rabiul Awal 1421 H atau 6 Juni 2000 M. di Surabaya dan kemudian mendapatkan badan Hukum Koperasi dari Kanwil Dinas Koperasi PK dan M Propinsi Jawa Timur dengan SK Nomor: 09/BH/KWK.13/VII/2000 tertanggal 22 Juli 2000. Produk di BMT UGT Sidogiri Waru ada dua yaitu: produk pembiayaan dan produk simpanan. Akad mudharabah di BMT Sidogiri digunakan pada produk simpanan yang terdiri dari tabungan umum syariah, tabungan haji al-haromain, tabungan umrah al-hasanah, tabungan idul fitri, tabungan qurban, tabungan lembaga peduli siswa, tabungan mudharabah berjangka, dan tabungan mudharabah berjangka plus. Berdasarkan analisis hukum Islam praktik mudharabah di BMT Sidogiri telah memenuhi rukun dan syarat mudharabah. Nasabah sebagai shahibul mal dan BMT sebagai mudharib, modal dan nisbah juga dijelaskan secara rinci di setiap produk, ijab qabul tertuang dalam akad dan BMT Sidogiri memiliki kewenangan mengelola dana nasabah. Kata Kunci: Mudharabah, BMT Sidogiri, Hukum Islam.